Profit-sharing as an incentive. Issue 20 (13th November 2019) - Hambly, Kym; Kumar, Rinu Vimal; Harcourt, Mark; Lam, Helen; Wood, Geoffrey
Abstract: Although profit-sharing is mostly associated with an economics perspective, its utilization as an employee incentive involves a psychological dimension, embedded in a broader socio-economic framework and reflected in organizational practices and management characteristics. The authors identify a list of conditions for profit-sharing's effectiveness as an incentive scheme, informed by three theories, expectancy theory, reinforcement theory and goal-setting theory, and supported by substantial evidence from the literature on profit-sharing. Thus, this paper provides critical information for profit-sharing's design and implementation, as well as offers some new practical insights into the contingencies and limitations of this incentive plan. Overall, it contributes to both theory and practice, integrating the three motivational frameworks regarding profit-sharing, and seeking to understand the insights such approaches afford to a socio-economic understanding.